A Migrated-mesenteric Lymphangioma: An Unusual Case of Intrabdominal Cystic Lesion in a New-born - Fatma Ceren Sarıoğlu; Orkun Sarıoğlu; Deniz Öztekin; Emel Tekin; Aslı Irmak Birancı; Özgür Öztekin (Journal of Pediatric Research, 2019)

(untitled)
Abdominal lymphangioma is a rare presentation of abdominal cystic lesions. They generally arise from small bowel mesentery. Migration of abdominal masses is an uncommon entity and usually occurs due to gossypiboma. There have been many reports of the radiologic appearance and unusual complications of mesenteric lymphangioma. However, to our knowledge, migration of mesenteric lymphangioma has not been reported in the literature. We present imaging findings of migrated-mesenteric lymphangioma from the intrauterine to postnatal period with histopathological correlation.